Effects of hyperbaric oxygen therapy on the viability of irradiated soft head and neck tissues in mice. (19th July 2013) - Spiegelberg, L; Braks, JAM; Djasim, UM; Farrell, E; van der, KGH; Wolvius, EB
<x xml:space="preserve">Abstract</x> Objectives Hyperbaric oxygen therapy (HBOT) is used clinically in irradiation‐induced injury to healthy tissues, but the effectiveness and working mechanism remain unclear. This study examined the effects of HBOT on irradiated salivary glands and tongue in a mouse model. Materials and Methods Mice were irradiated with a single dose (15 Gy) in the head and neck region and subjected to HBOT, either before or after irradiation. During the course of the treatments, salivary flow rates were measured and at different time points after radiation (2, 6, 10 and 24 weeks), salivary glands and tongue were harvested and (immuno) histochemically analysed. Results Proliferation and blood vessel density in salivary glands were enhanced by HBOT in the medium term (10 weeks after irradiation), while salivary flow rates were not influenced. In the long term, irradiation‐induced proliferation in the muscle tissue of the tongue was decreased by HBOT. Conclusion Hyperbaric oxygen therapy (HBOT) appears to stimulate regeneration or protection of salivary gland tissue following radiation therapy. Possible implications of the effect of HBOT on muscle tissue of the tongue for the prevention of dysphagia and trismus are discussed. This study provides insights on the cellular changes after HBOT and encourages further research on this topic to achieve a better implementation of the therapy in humans.